Escape orbit - Chiles, Patrick (Baen Publishing Enterprises, 2024)
"Five years ago, astronaut Jack Templeton took the spacecraft Magellan to the farthest reaches of our solar system, never to be heard from again. Until now. When the Magellan suddenly reappears where an undiscovered planet was suspected to be, it poses more questions than answers. How did Jack survive all this time? Can he be rescued before his life support runs out? And what is the object long thought to be the elusive "Planet Nine?" In a race against time, Jack's former crewmate Traci Keene spearheads a desperate effort to outfit a rescue mission. But she has competition. Agencies of both American and foreign governments have their own agendas, and rescuing rogue astronauts isn't among them. And at the edge of all that is known, a gateway to the unknown awaits. . . "--